A clinical study of hollow viscus injury due to blunt trauma abdomen - Kurane, Sanjot B.; Ugane, Subhod P. (International Journal of Research in Medical Sciences, 2017)
Background: Blunt trauma abdomen is one of the most common causes of morbidity and mortality among younger age group. Hollow viscus injury is one of the most common cause of mortality following blunt trauma abdomen. The Objective of this research was to study clinical presentation, diagnostic methods, treatment modalities and outcome of hollow viscus injury following blunt trauma abdomen. Methods: All patients with hollow viscus injury were included in this study, All the clinical, operative and postoperative parameters were recorded. It was a retrospective observational study. Results: Total number of patients with hollow viscus injury following blunt trauma abdomen were 15%. Amongst them 88.88% were males and remaining were females. The mean age of patients was 32 years. Road traffic accident was the most common cause of blunt trauma abdomen, seen in 72 % of patients. In 81.25% patients free gas under diaphragm was seen and remaining patients were diagnosed by ultrasonography. Ileum is most commonly site of perforation, and postoperative complications were seen in 66% of patients. Mortality was seen in 22.22% of patients. Conclusions: Hollow viscus injury following blunt trauma abdomen commonly seen in younger age group, and involves small bowel. Repeated clinical examination with appropriate imaging with multidisciplinary teamwork is the key for timely intervention for successful outcomes.